KNOW WANT LEARN STRATEGY TO IMPROVE STUDENTS’ READING COMPRHENSION STUDENTS’ OF SENIOR HIGH SCHOOL - Sitoresmi Hayuningtyas (English Education Department Slamet Riyadi University Surakarta, 2019)
Reading is a basic life skill of students success in school and consequently through life. Without the ability to read effectively, the students can not improve their reading skill. M.Ogle, the aims of the this research were to know whether Know Want Learn (KWL) strategy can improve students reading comprehension and to describe the class condition when Know Want Learn (KWL) strategy was implemented in teaching learning process at the Eleventh grade of SMA N Karangpanda in 2017/2018 Academic Year. This research was conducted at the Eleventh grade of SMA N Karangpandan. The method of the study was classroom action research which was conducted from March until May 2018. The data was collected through test and non-test. In collecting data was used multiple choices in pre test, post test 1, and post test 2. Besides that to collect non-test was used observation, interview, and documentation. While, to analyze the data was used t-test. The results of the research showed that the implementation of Know Want Learn (KWL) strategy was successful to improve students reading comprehension. The mean score increased from 57.92 in pre-test became 70 in post test 1 until 84.7 in post test 2. It can be concluded that Know Want Learn (KWL) strategy was appropriate to improve the students reading comprehension in teaching and learning process. Moreover, The class condition was more enjoyable, enthusiast, and conducive during learning process. Key words: Reading Comprehension; Know Want Learn (KWL) strategy; Classroom Action Research